Design Construction of Grains’ Chip Molder - Putri Candra Ayu; Saipul Bahri Daulay; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2015)
The processing of grains that contained starch into foodstuffs (chip) is an interesting thing to be known, one of the process is material’s pressing. The purpose of this research was to design, build, test and analyze the economic value of grains’ chip molder. The parameters observed were effective capacity, percentage of damaged material, organoleptic’s test and economic analysis. Based on this research, it was summarized that the effective capacity of the equipment was 2.82 kg/hour and the damaged material’s percentage was 8.07%. The color was categorized as 2 (white), the thickness was categorized as 1 (thin) and the flavor was categorized as 2 (medium). Economic analysis was as follows: basic costs for the first to the fifth year was Rp. 4,286.8/kg, Rp. 3,968.21/kg, Rp. 3,862.16/kg, Rp. 3,809.22/kg and Rp. 3,777.53/kg respectively. Break even point (BEP) for the first to the fifth year was 289.78 kg/year, 156.22 kg/year, 111.77 kg/year, 89.57 kg/year and 76.29 kg/year respectively. Internal rate of return (IRR) was 45.72%. Keywords : melinjo’s grain, molder,  pressing machine